Alternating polymer as well as synthesis method and application thereof
By designing an alternating polymer with a molecular main chain composed of alternate rigid and flexible fragments, combining Schiff base reaction and electrochemical redox reaction of ferrocene group/C=N bond group, the organic positive electrode of lithium battery is solved It is difficult to have the problem of rapid transmission of electrons and ions, and achieves the performance of lithium batteries with high energy density and power density.
Patent Information
- Application Number
- CN202411622604.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-14
AI Technical Summary
The organic positive electrode of lithium battery is difficult to have both electron transport and ion fast transport without damaging the electrode energy density.
An alternating polymer is used, whose molecular main chain is composed of rigid fragments and flexible fragments interphase, synthesized by Schiff base reaction, containing ferrocene groups and C=N bond groups as electroactive sites, which can be used without need. In the case of composite with conductive carbon materials, rapid transmission of electrons and ions is achieved.
It achieves rapid transmission performance of both electron and ions without damaging the electrode energy density, and improves the theoretical specific capacity, working voltage and cycling stability of lithium batteries.
Smart Images

Figure CN119463081A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium battery materials, and in particular relates to an alternating polymer having both rigid and flexible segments, a synthesis method thereof, and an application thereof in lithium battery positive electrode materials. Background Art
[0002] Rechargeable lithium batteries are the mainstay of portable electronics and the rapidly growing electric vehicle sector. The performance of lithium batteries is affected by the properties of the cathode materials. In recent years, with the growing demand for large-scale energy storage systems and electric vehicles, efforts have been devoted to developing high-performance cathode materials for lithium batteries. In particular, organic electrode materials have tunable molecular structures that enable rapid energy storage through redox reactions of active groups. Therefore, organic materials are promising candidates for the cathode of next-generation renewable lithium batteries due to their high capacity and rate performance.
[0003] Ion transport and electron transport determine the performance of organic electrodes. In order to improve the electronic conductivity of organic electrodes, large and rigid conjugated structures are usually designed to accelerate the transmission of electrons. However, the strong π-π interaction between the rigid conjugated structures makes the chains of linear polymers or the layers of two-dimensional layered polymers closely packed, which makes the active groups buried and ions difficult to quickly transport to the vicinity of the active groups. Slow electron or ion transport will result in unsatisfactory actual specific capacity and rate performance of organic electrodes.
[0004] In order to achieve high-performance organic electrodes for lithium batteries, the transport of ions and electrons in the electrodes must be accelerated and coordinated. At present, when preparing electrode materials, conductive materials such as composite carbon nanotubes or graphene are used to improve the electronic conductivity of the electrode and improve the stacking morphology to accelerate ion transport. For example, the research group of Chen Yongsheng of Nankai University prepared a composite active material ( Adv. Mater. 2023, 35, 2211152. ). After being compounded with conductive carbon materials, the electronic conductivity is improved and the stacking morphology of the original polymer is improved, so that electrons and ions can be quickly transmitted in the electrode, thereby obtaining a polymer organic positive electrode with high performance. However, these conductive carbon materials, as inactive materials, increase the mass of the overall electrode, which reduces the energy density and power density of the electrode. Therefore, it is extremely necessary to develop new methods to improve the problem of slow ion and electron transmission in organic electrodes without compromising the energy density of the electrode. Summary of the invention
[0005] In response to one or more of the above defects or improvement needs in the prior art, the present invention provides an alternating polymer, a synthesis method thereof and an application in a positive electrode material for a lithium battery, which solves the problem that an organic positive electrode for a lithium battery is difficult to achieve both electron transmission and rapid ion transmission without compromising the energy density of the electrode.
[0006] To achieve the above object, according to the first aspect of the present invention, an alternating polymer is provided, wherein the main molecular chain is composed of rigid segments and flexible segments alternately, wherein the rigid segments contain rigid benzene ring structures and ferrocene structures, and the flexible segments are ethyl structures; the structural formula of the alternating copolymer is shown in formula (I),
[0007] Formula (I) Wherein, the degree of polymerization n is an integer of 5 to 25.
[0008] As a further improvement of the present invention, the alternating copolymer is synthesized by using 1, 1'-ferrocene dicarboxaldehyde and 4, 4'-diaminobibenzyl as reaction monomers through a Schiff base reaction.
[0009] As a further improvement of the present invention, the alternating copolymer has ferrocene groups and C=N bond groups, and the ferrocene groups and C=N bond groups serve as electroactive sites and can undergo electrochemical redox reactions.
[0010] According to a second aspect of the present invention, there is provided a method for synthesizing an alternating copolymer, comprising the steps of: 1, 1'-ferrocene dicarboxaldehyde and 4, 4'-diaminobibenzyl are used as reaction monomers, and Schiff base reaction occurs after heating in the presence of a solvent to synthesize the alternating copolymer.
[0011] As a further improvement of the present invention, the molar ratio of 1,1'-ferrocene dicarboxaldehyde to 4,4'-diaminobibenzyl is 1-1.5:1; The concentrations of 1,1'-ferrocene dicarboxaldehyde and 4,4'-diaminobibenzyl in the reaction system are 0.05-0.1 mol / L, respectively.
[0012] As a further improvement of the present invention, the reaction system of the Schiff base reaction further comprises a catalyst, and the concentration of the catalyst in the reaction system is 0-2 mol / L.
[0013] As a further improvement of the present invention, the solvent is one or more of n-butanol, 1,4-dioxane, o-dichlorobenzene, and mesitylene.
[0014] As a further improvement of the present invention, the catalyst is acetic acid.
[0015] As a further improvement of the present invention, the temperature of the Schiff base reaction is 100-120° C., and the reaction time is 48-72 h.
[0016] According to the third aspect of the present invention, there is provided an application of an alternating copolymer in a positive electrode material of a lithium battery, using the alternating copolymer, or the alternating copolymer is obtained by the synthesis method; the lithium battery includes a lithium ion battery and a lithium metal battery.
[0017] In general, the above technical solution conceived by the present invention has the following beneficial effects compared with the prior art: (1) The alternating copolymer of the present invention contains both rigid conjugated segments that are beneficial to electron transport and flexible twisted segments that are beneficial to ion transport. The rigid-flexible structural design effectively avoids the shortcomings of fully rigid segments or fully flexible segments, while combining the advantages of both. The present invention can solve the problem that organic positive electrodes are difficult to achieve both rapid ion and electron transport without in-situ compounding with inactive conductive carbon materials. Therefore, the present invention can achieve both rapid electron and ion transport performance without compromising the electrode energy density.
[0018] (2) The alternating copolymer of the present invention uses ferrocene groups and C=N bond groups as active sites to achieve charge storage through the redox reaction of the two. When it is used as an organic positive electrode material for lithium batteries, multiple active sites provide 192 mAh g -1 The theoretical specific capacity of the ferrocene group is 2.5 times that of the anion as a charge carrier, which increases the operating voltage and has fast electrode reaction kinetics, ensuring the high energy density and power density of the polymer electrode.
[0019] (3) The alternating copolymer of the present invention contains a rigid conjugated structure, and the conjugated part has a π-π interaction, which effectively reduces its solubility in the organic electrolyte. When the alternating copolymer is used as an organic positive electrode material for lithium batteries, the problem of capacity reduction caused by dissolution is effectively avoided, which is beneficial to improving the cycle stability of the battery.
[0020] (4) The synthesis method of the alternating copolymer of the present invention is simple, with high yield and readily available raw materials, which helps to reduce the cost of commercial production. When used as a positive electrode material for lithium batteries, it exhibits excellent rate performance (the capacity at 10C is 60% of that at 0.5C, and the capacity at 50C is 40% of that at 0.5C), high active site utilization (active site utilization at 0.5C is 78%), and good cycle stability (the capacity retention rate is 60% after 3500 cycles at 10C). The present invention provides a new idea for constructing organic electrodes with excellent rate performance and high active site utilization, and is expected to be used as a positive electrode material for the next generation of lithium batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is the infrared spectrum of the alternating copolymer synthesized in Example 1 of the present invention; Figure 2The cyclic voltammetry curve of the alternating copolymer synthesized in Example 1 of the present invention when used as a positive electrode material for a lithium battery; Figure 3 The charge and discharge curve of the alternating copolymer synthesized in Example 1 of the present invention when used as a positive electrode material for a lithium battery; Figure 4 The rate performance of the alternating copolymer synthesized in Example 1 of the present invention when used as a positive electrode material for a lithium battery; Figure 5 The long cycle performance of the alternating copolymer synthesized in Example 1 of the present invention when used as a positive electrode material for a lithium battery. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and Examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other. Unless otherwise stated, the raw materials and reagents used in the following examples are all commercially available products, or can be prepared by known methods.
[0023] The present invention provides an alternating copolymer having both rigid and flexible segments, wherein the main molecular chain is composed of rigid segments and flexible segments alternately, wherein the rigid segments contain a rigid benzene ring structure and a ferrocene structure, and the flexible segments are ethyl structures. The structural formula of the alternating copolymer is shown in formula (I).
[0024] Formula (I).
[0025] Wherein, the degree of polymerization n is an integer of 5 to 25.
[0026] The alternating copolymer of the embodiment of the present invention contains both rigid conjugated segments that are beneficial to electron transmission and flexible twisted segments that are beneficial to ion transmission. The rigid-flexible structural design effectively avoids the shortcomings of all-rigid segments or all-flexible segments, while having the advantages of both, and can have both electron and ion rapid transmission performance without compromising the electrode energy density.
[0027] The alternating copolymer is synthesized by Schiff base reaction using 1, 1'-ferrocene dicarboxaldehyde and 4, 4'-diaminobibenzyl as reaction monomers. The alternating copolymer has ferrocene groups and C=N bond groups, which can undergo electrochemical redox reactions as electroactive sites, and realize charge storage through the redox reactions of the two.
[0028] The present invention also provides a method for synthesizing the above alternating copolymer, comprising the following steps: Using 1, 1'-ferrocene dicarboxaldehyde and 4, 4'-diaminobibenzyl as reaction monomers, in the presence of a solvent, a Schiff base reaction occurs after heating to synthesize an alternating copolymer as shown in formula (I).
[0029] The above synthesis reaction formula is shown in formula (II),
[0030] Formula (2).
[0031] In some embodiments, the molar ratio of 1,1'-ferrocene dicarboxaldehyde to 4,4'-diaminobibenzyl is 1 to 1.5: 1. The concentrations of 1,1'-ferrocene dicarboxaldehyde and 4,4'-diaminobibenzyl in the reaction system are 0.05 to 0.1 mol / L, respectively.
[0032] In some embodiments, the reaction system of the Schiff base reaction further comprises a catalyst, and the concentration of the catalyst in the reaction system is 0-2 mol / L.
[0033] In some embodiments, the solvent is one or more of n-butanol, 1,4-dioxane, o-dichlorobenzene, and mesitylene; and the catalyst is acetic acid.
[0034] In some embodiments, the temperature of the Schiff base reaction is 100-120° C., and the reaction time is 48-72 h.
[0035] In some specific embodiments of the present invention, the method for synthesizing the above alternating copolymer comprises the following steps: Mix 1, 1'-ferrocene dicarboxaldehyde and 4, 4'-diaminobibenzyl, add solvent and catalyst, heat to 100-120 °C, and react for 48-72 h; After the reaction is completed, the product is filtered, washed with an organic solvent (such as N, N-dimethylformamide, anhydrous methanol) that can dissolve the reaction monomers, and vacuum dried to obtain the alternating copolymer.
[0036] The present invention also provides an application of the alternating copolymer in a positive electrode material of a lithium battery, wherein the lithium battery includes a lithium ion battery and a lithium metal battery.
[0037] When the alternating copolymer is used as the positive electrode material of a lithium battery, the C=N bond group and the ferrocene group of the alternating copolymer serve as active sites, and charge storage is achieved through the redox reaction of the two. Its charge and discharge mechanism is shown in Formula (III):
[0038] Formula (III).
[0039] The assembled half-cells were 1.2-4.0 (vs. Li / Li + ) in the potential range. First, the charging step is carried out. When charged to the range of 3.2~3.6 V, ferrocene is oxidized to ferrocene ion. When fully charged (to 4.0 V), it is then discharged. When discharged to the range of 3.6~3.2 V, ferrocene ion is reduced to ferrocene; when discharged to the range of 2.4~2.0 V, C=N is reduced to CN-Li bond. When discharged completely (to 1.2 V), the charging process is continued. In the range of 2.0~2.4V, CN-Li bond is oxidized to C=N bond again; when charged to the range of 3.2~3.6 V, ferrocene is oxidized to ferrocene ion again, and the above steps are repeated in the subsequent discharge-charge process. During the charge and discharge process, a total of three electron redox reactions occurred in each repeating unit, providing 192 mAh g -1 The ferrocene group uses anions as charge carriers, which increases the operating voltage and has fast electrode reaction kinetics, ensuring high energy density and power density of the polymer electrode.
[0040] The following are examples: It should be noted that the alternating copolymer of the present invention is synthesized by Schiff base reaction using 1,1'-ferrocene dicarboxaldehyde and 4,4'-diaminobibenzyl as reaction monomers, and the synthesis process is based on a reversible linear polycondensation mechanism. For reversible linear polycondensation, the relative molecular mass of the polymer can be represented by the average degree of polymerization n, n=(1+r) / (1+r-2rP), where r is the molar ratio of the functional groups of the two monomers, and P is the degree of group reaction. In the alternating copolymer synthesized by the present invention, the degree of polymerization n is an integer of 5 to 25, and the degree of polymerization n of the alternating copolymers in the following examples are estimated by the above method.
[0041] Example 1 The alternating copolymer of this embodiment is synthesized according to the following steps: 1, 1'-ferrocene dicarboxaldehyde (48.4 mg, 0.2 mmol) and 4, 4'-diaminobibenzyl (42.4 mg, 0.2 mmol) were added to a pressure-resistant reaction bottle, followed by 2 mL of mesitylene and 2 mL of 1, 4-dioxane as reaction solvents, and 200 μL of acetic acid as a catalyst. The system was heated to 120 °C and reacted for 72 hours. After the reaction, the product was filtered out and washed with organic solvents such as N, N-dimethylformamide and anhydrous methanol that dissolve the monomers. After vacuum drying at 80 °C overnight, an alternating copolymer as shown in formula (I) was obtained, wherein n=5, and the final yield was 92%.
[0042] The infrared spectrum of the alternating copolymer synthesized in this example is as follows Figure 1 As shown, the infrared characteristic peaks of the amino monomer and the aldehyde monomer basically disappeared, indicating that the polymerization reaction was complete.
[0043] The alternating copolymer synthesized in this embodiment is used as the positive electrode material of the lithium battery, and is ground with a commercial conductive agent and a binder in a mass ratio of 6:3:1. After the powder is ground evenly, N, N-dimethylpyrrolidone is added drop by drop as a solvent while continuing to grind and mix until a uniform slurry with a certain fluidity is obtained. The slurry is then scraped on an aluminum foil with a scraper. Finally, the aluminum foil with the active slurry is dried and stamped into a pole piece, and the prepared pole piece is assembled with a commercial diaphragm and a lithium sheet into a lithium battery for performance testing.
[0044] The cyclic voltammetry curve of the lithium battery assembled with the alternating copolymer synthesized in this example as the positive electrode material at a scan rate of 0.1 mV / s is as follows: Figure 2 It was observed that the + / Li) with two pairs of redox peaks. The first one is attributed to Fe 2+ and Fe 3+ The conversion between Fe 3+ It is the p-type redox active part, which is related to the imine group of the n-type redox active part (Adv. Mater. 2023, 35, 2211152.). This shows that the alternating copolymer material has multiple electrochemical active sites, which can realize multi-electron transfer, thereby improving its theoretical capacity.
[0045] The alternating copolymer synthesized in this example was used as the positive electrode material to assemble a lithium battery at 0.5C (1C = 192 mAg -1 ) under the charge and discharge curves as shown in Figure 3 The results show that it can provide about 150 mAh g at 0.5 C. -1 The specific capacity corresponds to an active site utilization of 78%, which exceeds the corresponding values of polymer organic positive electrodes for lithium-ion batteries in many existing technologies, indicating that the electrode has a good electron transfer path.
[0046] The rate performance of the lithium battery assembled with the alternating copolymer synthesized in this example as the positive electrode material is as follows: Figure 4 The results show that the capacity decays slowly at high rates, with the capacity at 10C being 60% of that at 0.5C and the capacity at 50C being 40% of that at 0.5C, indicating that the electrode has fast electron and ion transfer rates. The excellent rate performance comes from the rigid and flexible structural design of the alternating copolymer.
[0047] The long cycle performance of the lithium battery assembled with the alternating copolymer synthesized in this example as the positive electrode material is as follows: Figure 5 The results show that the initial capacity at 10C is 90 mAh g -1 The capacity retention rate is 60% after 3500 cycles. The excellent cycle stability is due to the stable structure of the polymer.
[0048] Example 2 The synthesis of the alternating copolymer in this example is different from that in Example 1 only in that the amount of the reaction monomer, the amount of the solvent and the amount of the catalyst are increased by 10 times, and the other reaction conditions and steps are the same, to obtain an alternating copolymer of formula (I), wherein n is 15 and the yield is 90%.
[0049] The alternating copolymer obtained in this example was used as the positive electrode material of the lithium battery, and the preparation of the pole piece, battery assembly and performance test were carried out under the same conditions and steps as in Example 1. The performance of the polymer obtained in this example as the positive electrode material of the lithium battery was basically similar to that in Example 1.
[0050] Example 3 The synthesis of the alternating copolymer in this example is different from that in Example 1 only in the different ratios of the reaction monomers added, that is, in this example, 1, 1'-ferrocene dicarboxaldehyde (72.6 mg, 0.3 mmol) and 4, 4'-diaminobibenzyl (42.4 mg, 0.2 mmol) are used as reaction monomers, and other reaction conditions and steps are the same to obtain an alternating copolymer of formula (I), wherein n is 18 and the yield is 85%.
[0051] The alternating copolymer obtained in this example was used as the positive electrode material of the lithium battery, and the preparation of the pole piece, battery assembly and performance test were carried out under the same conditions and steps as in Example 1. The performance of the polymer obtained in this example as the positive electrode material of the lithium battery was basically similar to that in Example 1.
[0052] Example 4 The synthesis of the alternating copolymer in this example differs from that in Example 1 only in the amounts of the reaction monomers, solvents and catalysts. That is, in this example, 1, 1'-ferrocene dicarboxaldehyde (0.242 g, 1 mmol) and 4, 4'-diaminobibenzyl (0.242 mg, 1 mmol) are used as reaction monomers, the reaction solvent is 10 mL of n-butanol, the catalyst is 1 mL of acetic acid, the reaction time is 48 hours, the reaction temperature is 100 °C, and an alternating copolymer shown in formula (I) is obtained, wherein n is 25 and the yield is 87%.
[0053] The alternating copolymer obtained in this example was used as the positive electrode material of the lithium battery, and the preparation of the pole piece, battery assembly and performance test were carried out under the same conditions and steps as in Example 1. The performance of the polymer obtained in this example as the positive electrode material of the lithium battery was basically similar to that in Example 1.
[0054] Example 5 The synthesis of the alternating copolymer in this example is different from that in Example 1 only in that the solvent is changed to 4 mL of o-dichlorobenzene and the amount of acetic acid catalyst is changed to 450 μL, to obtain an alternating copolymer of formula (I), wherein n is 12 and the yield is 80%.
[0055] The alternating copolymer obtained in this example was used as a positive electrode material for a lithium ion battery, and the preparation of the pole piece, battery assembly and performance testing were carried out under the same conditions and steps as in Example 1. The performance of the polymer obtained in this example as a positive electrode material for a lithium battery was substantially similar to that in Example 1.
[0056] Example 6 The synthesis of the alternating copolymer in this example is different from that in Example 1 only in that no acetic acid catalyst is used to obtain an alternating copolymer of formula (I), wherein n is 5 and the yield is 78%.
[0057] The alternating copolymer obtained in this example was used as a positive electrode material for a lithium ion battery, and the preparation of the pole piece, battery assembly and performance testing were carried out under the same conditions and steps as in Example 1. The performance of the polymer obtained in this example as a positive electrode material for a lithium battery was substantially similar to that in Example 1.
[0058] The alternating copolymer of the embodiment of the present invention has a simple synthesis process, high yield, and can be mass-produced. When it is used as a positive electrode material for a lithium battery, the assembled lithium battery exhibits excellent rate performance, high specific capacity, and good long cycle performance, and has the potential to construct a new, environmentally friendly, and sustainable organic lithium battery.
[0059] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An alternating copolymer, characterized in that: The main chain of the molecule is composed of rigid segments and flexible segments alternately, wherein the rigid segments contain a rigid benzene ring structure and a ferrocene structure, and the flexible segments are ethyl structures; the structural formula of the alternating copolymer is shown in formula (I), Formula (I) Wherein, the degree of polymerization n is an integer of 5 to 25.
2. The alternating copolymer according to claim 1, characterized in that The alternating copolymer is synthesized by using 1, 1'-ferrocene dicarboxaldehyde and 4, 4'-diaminobibenzyl as reaction monomers through Schiff base reaction.
3. The alternating copolymer according to claim 1 or 2, characterized in that The alternating copolymer has ferrocene groups and C=N bond groups, and the ferrocene groups and C=N bond groups serve as electroactive sites and can undergo electrochemical redox reactions.
4. A method for synthesizing an alternating copolymer, for preparing the alternating copolymer according to any one of claims 1 to 3, characterized in that: The steps include: 1, 1'-ferrocene dicarboxaldehyde and 4, 4'-diaminobibenzyl are used as reaction monomers, and Schiff base reaction occurs after heating in the presence of a solvent to synthesize the alternating copolymer.
5. The synthesis method according to claim 4, characterized in that The molar ratio of 1,1'-ferrocene dicarboxaldehyde to 4,4'-diaminobibenzyl is 1-1.5:1; The concentrations of 1,1'-ferrocene dicarboxaldehyde and 4,4'-diaminobibenzyl in the reaction system are 0.05-0.1 mol / L, respectively.
6. The synthesis method according to claim 4 or 5, characterized in that The reaction system of the Schiff base reaction further comprises a catalyst, and the concentration of the catalyst in the reaction system is 0-2 mol / L.
7. The synthesis method according to claim 4 or 5, characterized in that: The solvent is one or more of n-butanol, 1,4-dioxane, o-dichlorobenzene, and mesitylene.
8. The synthesis method according to claim 6, characterized in that The catalyst is acetic acid.
9. The synthesis method according to claim 4 or 5, characterized in that: The temperature of the Schiff base reaction is 100-120° C., and the reaction time is 48-72 h.
10. Application of an alternating copolymer in a positive electrode material for a lithium battery, characterized in that: The alternating copolymer according to any one of claims 1 to 3 is used, or the alternating copolymer is obtained by the synthesis method according to any one of claims 4 to 9; the lithium battery includes a lithium ion battery and a lithium metal battery.
Citation Information
Patent Citations
Single-ion polymer, preparation method thereof and application of single-ion polymer in lithium ion battery positive electrode material
CN118005871A